THE IMPACT OF QUIZIZZ ON STUDENTS’ ENGLISH LEARNING MOTIVATION - Ardavi, Andi Ryaz Daviq; Atmowardoyo, Haryanto; Munir, Munir (JTechLP: Journal of Technology in Language Pedagogy, 2024)
In this study to be conducted by the researcher, the researcher aims to find out the impact of Quizizz on students’ English learning motivation. The samples of this study were five students of SMP Kartika XX-2 Makassar that have been chosen on purpose. This study used a descriptive analysis qualitative method. The main instrument for collecting data for this study was an interview. The result of this study showed that all the samples of SMP Kartika xx-2 Makassar were motivated to learn English when using the Quizizz application in class. The interview results got positive responses from all of the samples based on three indicators of Gardner’s motivation theory, as follows: willingness, eagerness, and enjoyment of learning. Based on the interview results, the samples answered that when the Quizizz application was applied to learning they felt willing to learn, feel eager, and also, they were enjoying the learning process. This can happen because the Quizizz application is practical/easy to use, the students don’t feel pressured when answering the task, doesn’t make the students feel bored, and how it is designed just like playing a game.  This study concludes that the Quizizz application has a good/positive impact on the student’s English learning motivation.